2018
DOI: 10.1016/j.precamres.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Shallow water anoxia in the Mesoproterozoic ocean: Evidence from the Bashkir Meganticlinorium, Southern Urals

Abstract: Article:Doyle, KA, Poulton, SW orcid.org/0000-0001-7621-189X, Newton, RJ orcid.org/0000-0003-0144-6867 et al. (2 more authors) (2018) Shallow water anoxia in the Mesoproterozoic ocean: Evidence from the Bashkir Meganticlinorium, Southern Urals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 110 publications
0
12
0
Order By: Relevance
“…For example, the “Canfield ocean” featured anoxic and euxinic (sulfide‐rich) deep‐ocean conditions through the Proterozoic, relieved only by a relatively unidirectional rise in oxygen during the late Ediacaran (Canfield, ). Broader stratigraphic and geographic coverage, including onshore–offshore transects, as well as new redox proxies have provided a more nuanced view of Proterozoic redox with much less stability (Diamond & Lyons, ; Doyle, Poulton, Newton, Podkovyrov, & Bekker, ; He et al, ; Li, Cheng, et al, ; Li, Zhang, et al, ; Planavsky, Cole, et al, ; Planavsky, Slack, et al, ; Sperling et al, ; Tang, Shi, Wang, & Jiang, ). Any attempts to model Proterozoic redox conditions are similarly left with the conclusion that the marine redox landscape was patchy and complicated (Reinhard, Planavsky, Olson, Lyons, & Erwin, ).…”
Section: Myths About Oxygen and The Rise Of Animalsmentioning
confidence: 99%
“…For example, the “Canfield ocean” featured anoxic and euxinic (sulfide‐rich) deep‐ocean conditions through the Proterozoic, relieved only by a relatively unidirectional rise in oxygen during the late Ediacaran (Canfield, ). Broader stratigraphic and geographic coverage, including onshore–offshore transects, as well as new redox proxies have provided a more nuanced view of Proterozoic redox with much less stability (Diamond & Lyons, ; Doyle, Poulton, Newton, Podkovyrov, & Bekker, ; He et al, ; Li, Cheng, et al, ; Li, Zhang, et al, ; Planavsky, Cole, et al, ; Planavsky, Slack, et al, ; Sperling et al, ; Tang, Shi, Wang, & Jiang, ). Any attempts to model Proterozoic redox conditions are similarly left with the conclusion that the marine redox landscape was patchy and complicated (Reinhard, Planavsky, Olson, Lyons, & Erwin, ).…”
Section: Myths About Oxygen and The Rise Of Animalsmentioning
confidence: 99%
“…Lake Cadagno is a shallow weakly euxinic system (Canfield et al, 2010), which may make it a reasonable analogue for past shallow-water systems (e.g. Doyle et al, 2018) where oxidised iron compounds from riverine runoff and atmospheric dust are deposited onto the upper ocean and sink to anoxic waters where phototrophic organisms reside.…”
Section: Comparison Of Water Column δ 56 Fe Profiles To Other Lake Systems and The Black Seamentioning
confidence: 99%
“…However, a compilation of iron speciation data from deeper Mesoproterozoic settings revealed dominantly ferruginous conditions (Planavsky et al, 2011)-a conclusion that has been confirmed by subsequent iron speciation studies (Sperling et al, 2015;Beghin et al, 2017;Doyle et al, 2018;Zhang et al, 2018). It seems, then, that the Mesoproterozoic oceans may have been weakly redoxbuffered with frequent fluctuation in space and time between euxinic and ferruginous conditions (Planavsky et al, 2018), with evidence for at least weakly and intermittently oxic conditions in the surface waters (e.g., Hardisty et al, 2017).…”
Section: Local Redox Conditionsmentioning
confidence: 87%
“…Despite potential linkages between oxygen and evolution, the redox state of Mesoproterozoic atmosphere and oceans remains poorly constrained. Previous iron speciation studies have reported mostly locally anoxic and iron-rich (ferruginous) conditions in subsurface waters (Planavsky et al, 2011;Sperling et al, 2015;Doyle et al, 2018;Zhang et al, 2018)-however, both oxic and sulfidic conditions have also been reported in epeiric sea, open shelf, and basinal settings (e.g., Shen et al, 2002;Gilleaudeau and Kah, 2013;Sperling et al, 2014;Cox et al, 2016). Predominantly low marine oxygen levels are also evidenced by muted enrichment of redox-sensitive trace metals in many Mesoproterozoic-aged shales (e.g., Scott et al, 2008), as well as by both molybdenum (Arnold et al, 2004;Kendall et al, 2011) and, potentially, uranium isotope (Gilleaudeau et al, 2019) data.…”
Section: Introductionmentioning
confidence: 99%